Tales of mystery and imagination - Poe, Edgar Allan (Nxb. Đồng Nai, 2009)
Locked doors, bricked-up alcoves and premature burial close in on Poe's narrators as they, like their victims, are cut off from light, air and human society. The "disordered chambers" of the author's mind resonate with archetypal, if extreme, psychological states; these 46 tales also present the incurable hoaxer and teller of excessively tall tales, a master of this difficult genre.